EGFR and HER2 receptor kinase signaling mediate epithelial cell invasion by Candida albicans during oropharyngeal infection - Zhu, Weidong (National Academy of Sciences, 2012)
The fungus Candida albicans is the major cause of oropharyngeal candidiasis (OPC). A key feature of this disease is fungal invasion of oral epithelial cells, a process that can occur by active penetration and fungal-induced endocytosis. Two invasins, Als3 and Ssa1, induce epithelial cell endocytosis of C. albicans, in part by binding to E-cadherin. However, inhibition of E-cadherin function only partially reduces C. albicans endocytosis, suggesting that there are additional epithelial cell receptors for this organism. Here, we show that the EGF receptor (EGFR) and HER2 function cooperatively to induce the endocytosis of C. albicans hyphae. EGFR and HER2 interact with C. albicans in an Als3- and Ssa1-dependent manner, and this interaction induces receptor autophosphorylation. Signaling through both EGFR and HER2 is required for maximal epithelial cell endocytosis of C. albicans in vitro. Importantly, oral infection with C. albicans stimulates the phosphorylation of EGFR and HER2 in the oral mucosa of mice, and treatment with a dual EGFR and HER2 kinase inhibitor significantly decreases this phosphorylation and reduces the severity of OPC. These results show the importance of EGFR and HER2 signaling in the pathogenesis of OPC and indicate the feasibility of treating candidal infections by targeting the host cell receptors with which the fungus interacts.